Analisis Kandungan Proksimat dan Mineral Esensial Dari Gastropoda Turbo setosus asal Perairan Pulau Lemukutan, Kalimantan Barat - Hasanah, Fadiah Amalia; Warsidah, Warsidah; Safitri, Ikha; Sofiana, Mega Sari Juane; Nurdiansyah, Syarif Irwan (Oseanologia, 2023)
Turbo setosus is a species of the gastropod class that has a wavy shell with circular lines on its surface. Because it is easy to find, this type of snail is widely used in the food sector. The nutritional value of Turbo setosus is also high so it has economic value. Proximate analysis and essential minerals are useful to determine the nutritional value contained. Gastropods were extracted using Soxhlet at a certain temperature to measure moisture content, fat content, ash content, and carbohydrates. To find out the number of carbohydrates, the by difference method is used. Meanwhile, to find out the amount of minerals contained using the Atomic Absorption Spectrophotometry (AAS) method.